Inclusive searches for squarks and gluinos with the ATLAS detector - Khoo Teng Jian (EPJ Web of Conferences, 2013)
Despite the absence of experimental evidence, weak scale supersymmetry remains one of the best motivated and studied Standard Model extensions. These proceedings summarise recent ATLAS results utilising the 7-8 TeV LHC datasets, obtained from inclusive searches for supersymmetric squarks and gluinos in events containing jets and missing transverse momentum, together with leptons, photons and b-jets. Limits are set in a range of supersymmetric scenarios including the CMSSM, mGMSB and GGM frameworks.